Pengaruh Penerapan Model Pembelajaran Discovery Learning dan Pemberian Motivasi oleh Guru terhadap Hasil Belajar Siswa - Nurhadi Nurhadi; Shilfia Alfitry (PALAPA, 2020)
This research is motivated by the initial problem of the still low student learning outcomes in Islamic religious education subjects. The data analysis technique of this study used a regression analysis method. This type of research is quantitative by using the Quasy Experiment method and uses the Nonequivalent Control Group Design research design. Based on the results of the study, the effect of the application of the discovery learning model to student learning outcomes shows that the tcount is greater than ttable both at the 5% significance level or the 1% significance level (2,000 <3,119> 2,660) this means that Ha is accepted and H0 is rejected, while the effect of giving Teacher motivation towards student learning outcomes shows that tcount is greater than ttable both at the significance level of 5% and the significant level of 1% (2,000 <4,090> 2,660). Motivation by the teacher together on student learning outcomes results are greater than t table both at the 5% significance level and 1% significance level (2,000 <3,191> 2,660) this means that Ha is accepted and H0 is rejected.